2003
DOI: 10.1074/jbc.m207420200
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Ligand-binding Pocket for the Human Prostacyclin Receptor

Abstract: The human prostacyclin receptor is a seven-transmembrane ␣-helical G-protein coupled receptor, which plays important roles in both vascular smooth muscle relaxation as well as prevention of blood coagulation. The position of the native ligand-binding pocket for prostacyclin as well as other derivatives of the 20-carbon eicosanoid, arachidonic acid, has yet to be determined. Through the use of prostanoid receptor sequence alignments, site-directed mutagenesis, and the 2.8-Å x-ray crystallographic structure of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 35 publications
(41 reference statements)
6
53
0
Order By: Relevance
“…The improved homology model based on the hybrid template predicts that EL2 could play an important role in anchoring a free fatty acid at GPR84 by means of a positively charged arginine. Given that phylogenetically GPR84 belongs to the prostanoid receptor subfamily, for which the positively charged residue is predicted to coordinate the negatively charged ligands, as exemplified by the prostacyclin receptor (Stitham et al 2003) it is suggested that GPR84 also could attract the anionic part of the ligand via a counter-charged residue. Figure 7.…”
Section: Gpr84mentioning
confidence: 99%
“…The improved homology model based on the hybrid template predicts that EL2 could play an important role in anchoring a free fatty acid at GPR84 by means of a positively charged arginine. Given that phylogenetically GPR84 belongs to the prostanoid receptor subfamily, for which the positively charged residue is predicted to coordinate the negatively charged ligands, as exemplified by the prostacyclin receptor (Stitham et al 2003) it is suggested that GPR84 also could attract the anionic part of the ligand via a counter-charged residue. Figure 7.…”
Section: Gpr84mentioning
confidence: 99%
“…Previous studies had shown that positively charged amino acids within the TM regions are essential for the binding and function of other GPCRs whose ligands contain a carboxylic acid group (Stitham et al, 2003;He et al, 2004;Tunaru et al, 2005;Sabirsh et al, 2006). This, together with the observation that uncharged ester derivatives of SCFAs are inactive at FFA2 and FFA3 (Le Poul et al, 2003), led Milligan's group to hypothesize that basic residues might also play a crucial role in the binding of SCFAs to their receptors (Stoddart et al, 2008a).…”
Section: Ffa2/ffa3 Receptor Structure and Signal Transductionmentioning
confidence: 99%
“…[15][16] Like other prostanoid receptors, the hIP has been categorized (based on sequence homology, ligand structure, and overall receptor functionality) as a class A rhodopsin-like GPCR, and shares many structural commonalities with rhodopsin, the class A representative and "prototypical" GPCR. These common traits can be divided into 3 major receptor domains: (1) the extracellular domain, consisting of a short amino N-terminal tail and 3 extracellular loops (exoloops); (2) a TM domain, comprised of 7-TM-spanning ␣-helices, whose upper third ␣-helices contain the putative binding pocket 17 ; and (3) the cytoplasmic or intracellular domain that is made up of 3 helix-joining intracellular loops (cytoloops), a fourth loop produced by lipid anchoring (palmitoylation) of intracellular cysteines, and a fairly lengthy carboxyl terminus ( Figure 1). Genetic variants may, therefore, have differential effects on binding, expression, and activation, dependent on localization within the protein structure, analogous to the retinitis pigmentosa rhodopsin mutations.…”
mentioning
confidence: 99%